Quantum fermions and quantum field theory from classical statistics - Wetterich, Christof (Arxiv, 2012)
An Ising-type classical statistical ensemble can describe the quantum physics of fermions if one chooses a particular law for the time evolution of the probability distribution. It accounts for the time evolution of a quantum field theory for Dirac particles in an external electromagnetic field. This yields in the non-relativistic one-particle limit the Schr\"odinger equation for a quantum particle in a potential. Interference or tunneling arise from classical probabilities.